Herstellung beanspruchungsangepasster Aluminiumblechhalbzeuge durch eine maßgeschneiderte Variation der Abkühlgeschwindigkeit nach Lösungsglühen - Lechner, Michael (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
Precipitation hardenable aluminum alloys currently belong to the most important lightweight materials. For this reason, they are applied in many fields of day-to-day life. However, the limited formability is still an unsolved challenge. Therefore, within this fundamental research project a new and innovative technique to improve formability of precipitation hardenable aluminum alloys was developed. Through the patented technology of Tailor Quenched Blanks, it is possible to achieve mechanical properties which are stress optimized for a required application, by applying a locally tailored quenching after solution heat treatmen